2018
DOI: 10.1111/1365-2656.12903
|View full text |Cite
|
Sign up to set email alerts
|

Land‐use change alters the mechanisms assembling rainforest mammal communities in Borneo

Abstract: The assembly of species communities at local scales is thought to be driven by environmental filtering, species interactions and spatial processes such as dispersal limitation. Little is known about how the relative balance of these drivers of community assembly changes along environmental gradients, especially man-made environmental gradients associated with land-use change. Using concurrent camera- and live-trapping, we investigated the local-scale assembly of mammal communities along a gradient of land-use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Therefore, better knowledge on assembly mechanisms might be useful to develop appropriate restoration policies. For example, Wearn et al 4 suggest that if environmental filtering is the dominant driver of assembly, then steps to restore habitat quality may be important. Alternatively, if dispersal limitation dominates assembly, then restoring landscape connectivity might be more important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, better knowledge on assembly mechanisms might be useful to develop appropriate restoration policies. For example, Wearn et al 4 suggest that if environmental filtering is the dominant driver of assembly, then steps to restore habitat quality may be important. Alternatively, if dispersal limitation dominates assembly, then restoring landscape connectivity might be more important.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our ability to understand the relative importance of these not mutually exclusive assembly mechanisms is critical, as they can have high impacts on the conservation of local biodiversity and ecological functions. For example, a poor knowledge about the drivers of community assembly limit our capacity to predict the consequences of land-use change on diversity, and to devise useful management interventions in man-made landscapes 4 .…”
mentioning
confidence: 99%
“…Disturbance has been hypothesized to weaken composition–environment relationships, for example by favouring a small pool of disturbance‐tolerant generalist species across the entire environmental gradient (Thompson, Carpenter, Cogbill, & Foster, 2013; Vellend et al., 2007). However, if disturbance regimes (type or intensity) are correlated with environmental gradients, disturbance might increase the strength of composition–environment relationships (Danneyrolles, Arseneault, & Bergeron, 2018; Hogan, Zimmerman, Uriarte, Turner, & Thompson, 2016; Wearn et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the dynamics of community assembly is critical for conservation strategies aiming to protect and restore tropical forests (Mayfield and Levine 2010;de Bello et al 2012;Fitzgerald et al 2017;Hung et al 2019). For example, communities driven by environmental filtering and competition (driven by limited resources) will potentially benefit more from conservation management focused on improving habitat quality and structure (Wearn et al 2018). Previous research has revealed significant impacts of tropical habitat modifications on community assembly of ants, understorey plants and small mammals in Malaysia (Fayle et al 2013;Döbert et al 2017;Wearn et al 2018), dung beetles in Brazil (Audino et al 2017), and trees in China (Ding et al 2012).…”
Section: Introductionmentioning
confidence: 99%